Nutritional Sustainability via Positive Deviance: Challenges for Teaching, Research and Extension - Iorungwa, Agwa Samuel; Terhemba, Iombor Theophilus (Pakistan Journal of Nutrition, 2009)
Indices of malnutrition, maternal morbidity and mortality, alongside rampancy of diseases and food insecurity are still major challenges confronting Nigeria and indeed the developing world. Positive Deviance (PD) is one developmental approach that seeks to identify and optimize existing resources and solutions within the community to solve community problems, without brining in “alien” handouts developed without communities socio-cultural and economic considerations. This approach, identifies people or groups within communities who share in the same resources with the rest of the community, but are however able to uniquely enhance a more better and sustainable standard of living. This paper examines how PD works and notes major milestones of PD, especially in the spheres of nutrition, nothing equally the constraining challenges to PD. Relevance of PD on target directions of related Millennium Development Goals (MDGs) is positively highlighted. The need for nutritionists and academics to seek collaborative links with research institutions as well as government and non-governmental partnerships in driving this bottom-top developmental initiative in research and extension endeavors is one strong recommendation noted, amongst others.